Analisis Pemerolehan Bahasa Pertama Pada Anak Usia Lima Tahun Melalui Ilmu Linguistik - Septianingsih, Reno; Riantiarna, Ratna; Aulia Mufidha, Tiara; Handhayani, Suci; Saputra, Saputra; Fauziah, Muhardila (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to analyze language acquisition in children, obtained directly and supported by several factors, such as internal factors from both parents. The initial language acquisition in children is found and obtained from their mother. The research method used is qualitative descriptive. The data collection techniques employed are observation and interviews. The research subject is a five-year-old male child. The results of the study indicate that the initial language acquisition in a five-year-old child is obtained through interactions with their mother. At this age, the child can utter several words and sentences commonly used in their communication with family and friends. However, the language proficiency of the five-year-old is somewhat unclear in terms of the original words and sentences. Interactions in the child's environment influence language proficiency and vocabulary knowledge. The child uses both Indonesian and a mixture of regional languages in daily communication, both at home and at school. The child acquires new knowledge about various words through school, reading books, and watching videos on YouTube.